Study of Development Philosophy of Indonesian Archery Sports (Study at the National Sports Museum) - Suffa, Yunita Fella; Hartono, Mugiyo; Soenyoto, Tommy (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The National Sports Museum is a place to showcase the tools used by sports fighters in the world. Sports philosophy is more precisely emphasized the problem of attitude, behavior, values, and morals, human beings with the problems that often arise and in the practices of sports activities. The problem statement is to find out: (1) What is the archery sports philosophy at the National Sports Museum? (2) How is the development of Indonesian archery at the National Sports Museum? Analyze the philosophy of the development of Indonesian Archery Sports at the National Sports Museum. Archery is a sport that uses a tool called a bow and arrow and a target board that makes it the center. The achievements of archery were proven by Donald Pandiangan athletes and 3 Srikandi Lilies Handayani, Nurfitriyana S. Lantang, and Kusuma Wardhani who won the Silver Medal at the 1988 Seoul Olympics. The method used is descriptive qualitative research. Library research with a descriptive philosophy approach whose material objects are human and environment. This library research is to be able to understand philosophically about human and environmental relations. The beginning of Archery development in Indonesia which became a matter of pride made a new spirit for Indonesia. Inconsistency, management, and the talent that the team possesses have produced extraordinary results. Making Archery the glory of the Srikandi Trio. Although the Archery after the Srikandi Trio suffered a downturn Indonesian archery managed to experience rapid development, the increase was seen in 2010 until now. Some regions and clubs still maintain traditional/jemparingan numbers as Indonesian culture which need to be maintained and developed on par with other numbers. The development of archery sports has also been included in school extracurricular activities.